2021
DOI: 10.1186/s12883-020-02041-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral symmetrical deep gray matter involvement and leptomeningeal enhancement in a child with MOG-IgG-associated encephalomyelitis

Abstract: Background Currently, myelin oligodendrocyte glycoprotein (MOG)-IgG-associated encephalomyelitis (MOG-EM) is regarded as an independent inflammatory demyelinating disease. Magnetic resonance imaging (MRI) abnormalities occur in 44.4% of patients with MOG-EM. However, symmetrical deep gray matter involvement with leptomeningeal enhancement is rarely described in the literature. Case presentation A 3-year-old boy was admitted to our hospital because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, 7 cases of MOG-AD-associated meningitis, which were described to have fever, nausea, and nuchal rigidity, have been reported including our case ( Table ) ( 10 - 16 ). The mean age of these patients was 24.4 years (range: 3-55); four of these patients were male.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…To the best of our knowledge, 7 cases of MOG-AD-associated meningitis, which were described to have fever, nausea, and nuchal rigidity, have been reported including our case ( Table ) ( 10 - 16 ). The mean age of these patients was 24.4 years (range: 3-55); four of these patients were male.…”
Section: Discussionmentioning
confidence: 77%
“…Meningeal involvement may possibly occur as sequelae associated encephalitis because MOG-AD frequently presents with encephalitis. However, one case ( 16 ) had only subcortical encephalitis, it possibly means that inflammation spread to the meninges. Another potential mechanism is the spread of inflammation from the meninges to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, LME was reported in only a small number of case reports, rarely described in children with MOG-E ( 22 24 ), and considered to be an atypical MRI finding of MOG-E ( 25 27 ). In the current study, we found that LME in MOG-E is common on CE-FLAIR.…”
Section: Discussionmentioning
confidence: 99%
“…However, few anti-MOG-positive cases have been reported with leptomeningeal involvement as case reports in the literature. Reported rare cases with leptomeningeal involvement are associated with cranial leptomeningeal involvement [13][14][15].…”
Section: Discussionmentioning
confidence: 99%